Evaluation of Antimicrobial Efficacy of Calcium Hypochlorite as an Endodontic Irrigant on a Mixed-culture Biofilm: An Ex vivo Study - Shadmehr, Elham; Davoudi, Amin; Sarmast, Nima Damoon; Saatchi, Masoud (Iranian Endodontic Journal, 2019)
Introduction: Calcium hypochlorite (CH) has been recently suggested as an endodontic irrigant. The aim of this investigation was to evaluate the antimicrobial efficacy of CH compared to sodium hypochlorite (NaOCl) and chlorhexidine (CHX) against multispecies biofilm in surface and deep dentinal tubules. Methods and Materials: Minimal inhibitory concentration (MIC) of irrigant agents was assessed using a microdilution method. One hundred and twenty of human maxillary incisor teeth were prepared and infected with suspension of Entrococcus faecalis, Fusobacterium nucleatum and Prevotella intermedia in an anaerobic jar for 7 days. Depending on irrigation solutions, specimens were divided into 4 groups (n=30); group 1: 2% CHX, group 2: 5.25% sodium hypochlorite, group 3: 5% calcium hypochlorite, group 4: positive control (normal saline (NS)). Fifteen remained specimens were used as negative control. Surviving bacteria were sampled before (S1) and after irrigation from surface (S2) and deep (S3) dentin. The medium turbidity was visualized with spectrophotometry. Data were analyzed using analysis of variance followed by Tukey post hoc test (α=0.05). Results: The MIC of CH against E. faecalis, F. nucleatum and P. intermedia was 25, 8 and 7.5 µg/mL respectively. There were no significant differences in S1 among the test groups. Moreover, 2% CHX and 5% CH had significantly lower medium turbidity at both S2 and S3, in comparison with 5.25% NaOCl (P=0.018 and 0.031, respectively). But there were no significant differences between 2% CHX and 5% CH at both S2 and S3 (P=0.862 and 0.978, respectively). Conclusion: Under the conditions of this ex vivo study, 5% CH and 2% CHX are more effective than 5.25% NaOCl in the reduction of mixed-culture biofilm. Keywords: Calcium Hypochlorite; Chlorhexidine; Endodontics; Sodium Hypochlorite